2011
DOI: 10.1074/jbc.m111.272377
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Utilization by Candida albicans Requires a Functional Glutathione Degradation (DUG) Pathway and OPT7, an Unusual Member of the Oligopeptide Transporter Family

Abstract: Background: Glutathione biosynthesis is essential for pathogenesis in Candida albicans. Exogenous glutathione utilization is not known. Results:The DUG pathway of glutathione degradation and an unusual transporter, OPT7, function in glutathione utilization. Conclusion: Glutathione utilization is efficient but not essential for survival in vivo. Significance: It enables one to understand how this pathway contributes toward homeostasis of redox and sulfur in a yeast pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…S. cerevisiae lacking c-glutamyl cysteine synthase (Gsh1), the first enzyme in glutathione biosynthesis, leads to glutathione autotrophy in which the cells dependent on exogenous GSH for its growth and survival [63,64]. In the absence of endogenous GSH, yeast has the ability to uptake GSH from an environment through high-affinity glutathione transporters such as Hgt1 [6365]. In the present study, we also demonstrated that gsh1Δ and gsh2Δ homozygous deletion strains has relatively low amount of basal GSH when compared to wild type and the counterpart heterozygous deletion strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. cerevisiae lacking c-glutamyl cysteine synthase (Gsh1), the first enzyme in glutathione biosynthesis, leads to glutathione autotrophy in which the cells dependent on exogenous GSH for its growth and survival [63,64]. In the absence of endogenous GSH, yeast has the ability to uptake GSH from an environment through high-affinity glutathione transporters such as Hgt1 [6365]. In the present study, we also demonstrated that gsh1Δ and gsh2Δ homozygous deletion strains has relatively low amount of basal GSH when compared to wild type and the counterpart heterozygous deletion strains.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of low amount of GSH in these deletion strains was further depleted by ebselen treatment and in turn places cells in oxidative stress. Importance and essentiality of GSH has also been demonstrated in other fungi species including Candida [60,65], suggesting that glutathione might form an attractive novel target for the development of new antifungal drugs [6668]. Future studies are required to delineate the interaction between ebselen and yeast GSH, and also the affinity of ebselen towards mammalian GSH.…”
Section: Discussionmentioning
confidence: 99%
“…However, our knowledge on the role of sulphur metabolism for fungal virulence has remained scarce. Only two studies have specifically addressed the importance of the sulphur-containing molecule glutathione in C. albicans and C. glabrata to demonstrate that glutathione biosynthesis, but not its uptake or degradation, is essential for virulence [23]. Accordingly, glutathione appears not to be the sulphur source these Candida species exploit in vivo , and its relevance for pathogenesis is probably due to its impact on iron metabolism [72].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have addressed its relevance for fungal virulence so far, focusing on synthesis and utilization of the sulphur-containing molecule glutathione in Candida albicans or C. glabrata [23], [24]. The importance of sulphur metabolism for aspergillosis has not been addressed to date.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that at least OPT1 to OPT5 encode functional peptide transporters, while Opt6 to Opt8 might have a more specific, narrower substrate spectrum that is not sufficient to allow growth on peptides generated by SAP-mediated digestion of BSA (6). Indeed, OPT7 has recently been found to encode a glutathione transporter (17).…”
mentioning
confidence: 99%